2011
DOI: 10.1029/2010gc003398
|View full text |Cite
|
Sign up to set email alerts
|

Lateral constrictional flow of hot orogenic crust: Insights from the Neoarchean of south India, geological and geophysical implications for orogenic plateaux

Abstract: [1] This study provides an in situ geological perspective on fabrics produced by synconvergence lateral crustal flow of hot orogens. It is based on the example of the Neoarchean orogen of the Dharwar craton (India) and combines structural analysis and ion microprobe U-Pb zircon geochronology. We document a pervasive, three-dimensional flow mode of the lower crust, called lateral constrictional flow (LCF), which combines orogen-normal shortening, lateral constrictional stretching, and transtension. LCF achieves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 197 publications
(137 citation statements)
references
References 73 publications
10
127
0
Order By: Relevance
“…The evolution of Chitradurga shear zone is still unanswered in the tectonic context of Dharwar craton. Recently, Chardon et al (2011) verified that the Chitradurga shear zone was obviously active between 2.56-2.50 Ga. All the three dated granitoids in the current study are older that this period, it can be suggested that the Chitradurga shear zone must be developed after the magmatic activity in the study area. Furthermore, field observations such as the development of sheared amphibolites and granitoids, solid state shear fabrics, layer-parallel/intrafolial folds etc.…”
Section: Constraint On the Formation Of The Chitradurga Shear Zonementioning
confidence: 85%
See 4 more Smart Citations
“…The evolution of Chitradurga shear zone is still unanswered in the tectonic context of Dharwar craton. Recently, Chardon et al (2011) verified that the Chitradurga shear zone was obviously active between 2.56-2.50 Ga. All the three dated granitoids in the current study are older that this period, it can be suggested that the Chitradurga shear zone must be developed after the magmatic activity in the study area. Furthermore, field observations such as the development of sheared amphibolites and granitoids, solid state shear fabrics, layer-parallel/intrafolial folds etc.…”
Section: Constraint On the Formation Of The Chitradurga Shear Zonementioning
confidence: 85%
“…All the data clearly suggest that Peninsular Gneiss was formed between 3.4-3.1 Ga and the older granitoid activity in the study area is contemporaneous with the formation of Peninsular Gneiss of TTG composition. The geochronological data in and around Chitradurga are in the age range of 2650-2550 Ma (Chadwick et al, 2007;Chardon et al, 2011;Jayananda et al, 2006;Taylor et al, 1984;Ram Mohan et al, 2014;Sarma et al, 2011), suggestive of a protracted magmatic episode in this region (Fig. 1a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations